LE-Probale Model through Nila's Edumath Interactive Mobile Learning to Improve Mathematical Literacy - Ubaidah, Nila; Zaenuri; Iwan Junaedi; Sugiman (Hipotenusa: Journal of Mathematical Society, 2024)
Creating a supportive learning environment through psychological well-being is an important indicator in achieving true happiness in the learning process, and also through project-based learning so that it plays an important role in the learning environment and the results are very real. The aim of this research is to produce the LE-Probale model syntax. The learning model components used adopt Joyce and Weil. The quality of the product developed is evaluated based on product development evaluations developed by Plomp and Neeven, which include validity by validators, practicality and effectiveness of field trials by observers. The realization of the model syntax consists of ten stages, namely: 1) Preparing an adequate learning environment; 2) Delivery of learning objectives; 3) Selecting learning materials and determining topics that students must study inductively (from examples then generalizing); 4) Meaningful understanding is linked to everyday life; 5) Provide trigger questions to observe and solve; 6) Group formation; 7) Design and complete projects related to other subjects with the help of Nila's Islamic Edumath Interactive Mobile Learning; 8) Rearrange and compare representations of project results; 9) Evaluate the resulting projects; 10) Teacher and student reflection to look back at the learning that has taken place.